Application of GSVD‐based precoding in MIMO‐NOMA relaying systems. Issue 21 (16th February 2021) - Rao, Chenguang; Ding, Zhiguo; Dai, Xuchu
Abstract : In this study, a simple two‐user multiple‐input multiple‐output (MIMO) relaying scenario is considered. To efficiently exploit the spectrum resources, a generalised singular value decomposition (GSVD) based precoding scheme with non‐orthogonal multiple access (NOMA) is proposed, which converts the multiple channels into several parallel single channels. The performance of the proposed GSVD‐MIMO relaying scheme is evaluated by using the distribution characteristics of squared generalised singular values of two users' channel matrices and the eigenvalues of the relay's channel matrix to obtain the expressions of the average data rate and outage probabilities. Both the asymptotic case and a practical scenario with nodes equipped with finite numbers of antennas are analysed because the distribution characteristics of squared generalised singular values in the two cases are different. Two special cases, single‐input multiple‐output and multiple‐input single‐output are considered. Simulation experiments are carried out to verify the effectiveness and accuracy of the obtained analytical results.